ANALISIS STRATEGI BISNIS PT SOHO INDUSTRI PHARMASI REGULAR - , ANNA KARINA ALGUSTIE ([Yogyakarta] : Universitas Gadjah Mada, 2012)
A competitive company is a company which has and implements business strategies that can act in response to external conditions and improve their internal capabilities. The objectives of this study are to identify and evaluate whether the company business strategy is suitable with its external and internal conditions and to arrange alternative strategies based on external and internal conditions. The research was a descriptive analysis. The data were collected through deep interviews and internal observation to the company, also supporting data from secondary source. The data were analyzed by: External and internal analysis with External Factors Evaluation Matrix and Internal Factors Evaluation Matrix